Work-Family Conflict and Employee Job Satisfaction: A Comparison of State-Owned and Foreign-Invested Enterprises in Vietnam - Linh, Nguyen Thi Thuy; Jin, Teh Choon; Kiong, Tee Poh; Fah, Benjamin Chan Yin (Journal of Asian Business Strategy, 2016)
Work and family issues have been long discussed in academic and practices. Work affects family and personal life and vice versa. The relationship of work and family could lead to positive consequences (e.g. Improved skills, morale) or negative consequences (e.g. Conflict, strain, exhaustion) to employees. The aims of this paper is to investigate the effects of work-family conflict on job satisfaction and compare the differences between employees working in State-owned enterprises (SOEs) and Foreign-invested enterprises (FIEs) in Vietnam. Respondents for this study were obtained from 49 employees from SOEs and 35 employees from FIEs in Vietnam. Descriptive analysis, independent-sample t-test and hierarchical regression analysis were conducted to analyse the data. The results of the study reveal that job satisfaction were found to be significantly different, but work-to-family conflict and family-to-work conflict were not significantly differ between the employees from SOEs and FIEs. Moreover, work-to-family conflict (WIF) and family-to-work (FIW) conflict are not the significant predictors for employee job satisfaction in both enterprises. The findings suggest that cultural value affects the link between work-family conflict and job satisfaction to some extent. Research limitation and recommendation for future research on this topic were discussed.